Split Applications of Coyote and Lumax for Efficacy in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
In an effort to determine the efficacy of herbicide application timing in sorghum, full herbicide rates were applied 14 days preplant, and compared with split applications of half rates applied at two timings. Generally, weed control was best when half of the labeled rates were applied 14 days preplant followed by the other half preemergence, compared to full rates applied 14 days preplant. However, control of velvetleaf and common sunflower was excellent (95% or more) regardless of when the treatments were applied. Grain sorghum yields were similar among all herbicide treatments, and each treatment increased yield from 2 to 2.5-fold relative to the nontreated controls.
Keywords: residual control; sequential applications